Phenotypic and genotypic diversity among Astragalus species growing in eastern Anatolia region of Turkey - Agar, Guleray; Adiguzel, Ahmet; Baris, Ozlem; Gulluce, Medine; Sahin, Fikrettin; Sengul, Meryem (Bangladesh Journal of Botany, 2010)
Fatty acid (FA) and RAPD profiles were used to examine phenotypic and genotypic relationships, respectively among Astragalus atrocarpus, A. campylosema subsp. campylosema, A. fumosus, A. galegiformes, A. lineatus var. jildisianus and A. trichostigma. All the taxa were separated based on the presence and composition of 33 different FAs. A set of nine FAs (14 : 0, 16 : 0, 18 : 0, 18 N alcohol, 17 : 1 iso G, 18: 1 : ω8c, C18 : 1 : ω9t alcohol, 18 : 2 : ω6c, 19 : 1: ω6c) were found in all Astragalus taxa. Six of the ten decamer primers examined were selected to explore the genetic variation among the taxa tested. The RAPD results suggested that A. fumosus, A. lineatus and A. trichostigma are closely related and completely different from the rest of the taxa. Four genetically distinct groups were found among the species. High genetic variations were present among species growing wildly in eastern Anatolia region of Turkey, which may imply differences in their origin. It appears that both RAPD and FA analyses are useful for differentiation of Astragalus species. Keywords: Astragalus spp.; Genotypic; Phenotypic; Diversity; FAMEs; RAPD; Turkey DOI: 10.3329/bjb.v39i1.5518 Bangladesh J. Bot. 39(1): 1-7, 2010 (June)